2016
DOI: 10.1080/23328940.2016.1214334
|View full text |Cite
|
Sign up to set email alerts
|

How to keep cool in a hot desert: Torpor in two species of free-ranging bats in summer

Abstract: Small insectivorous tree-roosting bats are among the most taxonomically diverse group of mammals in Australia's desert, yet little is known about their thermal physiology, torpor patterns and roosting ecology, especially during summer. We used temperature-telemetry to quantify and compare thermal biology and roost selection by broad-nosed bats Scotorepens greyii (6.3 g; n = 11) and Scotorepens balstoni (9.9 g; n = 5) in Sturt National Park (NSW Australia) over 3 summers (2010–13). Both vespertilionids used tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…When small mammals are euthermic and confronted with T a near the upper critical temperature, excess heat generated by metabolism or activity and the absorption of heat from the environment can quickly exceed their thermoregulatory capacities. Other tropical bats enter extended torpor, but only in the cooler morning hours and always accompanied by a reduction in body temperature, probably to save water in anticipation of responding to afternoon heat [33,34]. By contrast, M. commersoni entered hot torpor only under heat stress and maintained micro-bouts during cooler daytimes.…”
Section: Two Novel Modes Of Torpormentioning
confidence: 99%
“…When small mammals are euthermic and confronted with T a near the upper critical temperature, excess heat generated by metabolism or activity and the absorption of heat from the environment can quickly exceed their thermoregulatory capacities. Other tropical bats enter extended torpor, but only in the cooler morning hours and always accompanied by a reduction in body temperature, probably to save water in anticipation of responding to afternoon heat [33,34]. By contrast, M. commersoni entered hot torpor only under heat stress and maintained micro-bouts during cooler daytimes.…”
Section: Two Novel Modes Of Torpormentioning
confidence: 99%
“…24°C: [15][16][17]) or at night [18,19]. However, desert-dwelling species and others in hot climates may enter torpor at T a greater than 30°C [18,20]. The high T a s at which these bats begin to thermoconform approach the normal homoeothermic body temperature of most mammals (ca 36-38°C).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, Pavey et al (2020) suggested that the ability of dasyurids to enter torpor to save energy may decouple population dynamics from rainfall-driven primary productivity. Bats also use torpor on a regular basis, both after fire (Doty et al 2016) and in hot, dry environments (Bondarenco et al 2016), and this may reduce the effect of lower productivity during droughts on populations.…”
Section: Discussionmentioning
confidence: 99%
“…2016) and in hot, dry environments (Bondarenco et al . 2016), and this may reduce the effect of lower productivity during droughts on populations.…”
Section: Discussionmentioning
confidence: 99%